The Campanha Gaúcha region, Brazil: features and agricultural transformations 1950-2020 - Manfio, Vanessa (Latin American Journal of Rural Studies, 2020)
The Campanha Gaúcha is a region of cattle ranching tradition that in recent years has undergone profound agrarian transformations that have changed regional landscapes and created economic and business diversity. This diversity has been important for the region to pursue economic and social development. Therefore, this article aims to discuss the agrarian transformations that occurred in the region from 1950 to 2020, in order to contribute to the agrarian studies of Rio Grande do Sul and Campanha Gaúcha. For this, we used the qualitative approach and the literature review, in order to reach a debate that perpetrates the analysis of the main activities developed regionally. However, the region is in a moment of economic growth and worldwide visibility in face of the new activities that are being implemented.